TRANSITION ZONE IN SELJUQ DOME CHAMBERS - Moradi, Amin (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2020)
Architecturally, the Seljuqs' dominion makes a significant shift from the Pre-Islamic Sassanid squinches into a sophisticated transition mechanism employed to change the walls of a square chamber to an octagonal base to set a dome. It initiated a new construction methodology to hybridize the previous experiences of Sassanid domes with new architectural tendencies since the prior understanding of the transition zone was a makeshift in quality. It is not consistent enough for future architectural adventures in creating larger structures. Although a cursory investigation of transition zones of Seljuq dome chambers in some respects reveals a relatively homogeneous framework, it has never meant the stagnation of architectural creativity in different parts of the Seljuk territory. On the other hand, the typology and local schools of Seljuq transition zones of dome chambers have not been thoroughly considered by geographical centralism in Iran. For a better understanding of the standardization of various techniques considered in Seljuq architecture between the 11th and 12th centuries to span the cubic structure to a circular plan, this project is aimed to clarify three different schools of architectural articulation concerning transition zone in the Seljuq dome chambers. A structural analysis was conducted assuming several scenarios over Seljuq domes to clarify its geographical characteristics as well as static behaviors in different parts of Iran. This study shows that no dome has a regular mechanism of a transition zone, no two regions share the same approach, and three different empirical attitudes towards the transition zone would be enough to consider three architectural schools encompassing Northwest Iran, Alborz, and Central Iran, in which the difference lies in the basic elements of the construction of the transition zone rather than proportions.